Mathematics Literacy: An Australian Perspective and Experience - Allan Leslie White (Southeast Asian Mathematics Education Journal, 2017)
A brief listing of five different types of mathematical literacy is provided. The definition used by the Program for International Student Assessment (PISA) is selected and some brief remarks are provided on this program. The performance of Australian students is examined which shows that at the beginning of the new century 2000, Australian educators were feeling comfortable and reasonably satisfied with student performance but by 2016there was great concern over a consistent decline. The reasons for this decline are briefly discussed with the focus on Australian governmental policies that followed the directions of reform in the United States and Great Britain, and what has been labelled GERM. Current policies have been tried and failed and it is time to look for alternatives. While it is not wise to just copy the programs and policies of another country rather than adapt them due to differences in culture, population diversity, and other factors, nevertheless countries such as Finland can offer alternative paths to be explored. In Australia’s case it would also seem to be unwise to adopt policies and programs of countries who perform worse than it.